Prevalence of overweight and obesity among rural early adolescents in central part of Vidarbha, Maharashtra- A Cross Sectional study - Prajapati, Kshatrapal; Nayak, Smrutiranjan; Dhande, Nikhil; Mudey, Abhay (International Journal of Medical Research and Review, 2017)
Background: According to W.H.O number of over-weight children under the age group of five was estimated to be over 42 million and nearly close to 35 million of these were living in developing countries. Obesity in children and adolescents is defined as a BMI greater than the 95th percentile. Objective: To find out the prevalence of overweight and obesity in school going early adolescents. 2) To find out the factors contributing to early adolescent overweight/obesity. Method: School-going children between 11-15yrs. A cross-sectional (observational) study was carried out in middle- schools (5th to 7th standard) and high-schools (8th to 10th standard) of Alphonsa High School of Sawangi. Result: Prevalence of over-weight in early adolescent was found to be 15.83% and obese was 11.18%. Obese school going students who watched television for 1 hour were 02.48%, those watching TV for 2 hours were 03.72% and more than 2 hours were 04.96%. Obesity was found to be more in children watching television for longer duration. Conclusion: Overweight/obesity among children are progressing towards epidemic level. Eating habit of junk food is on rise.